In-vitro investigation of anticoagulant activities in edible and medicinal mushrooms / Teo Chiew Phin - Teo, Chiew Phin (2014)
Six mushroom samples (Ganoderma lucidum, Cordyceps militaris, Lignosus rhinocerotis, Pleurotus giganteus, Pleurotus floridanus and Auricularia polytricha) were screened for their anticoagulant activity. Mushroom samples provided were freeze-dried and blended into powder form. Different concentrations of aqueous mushroom extracts were added to one ml of fresh bovine blood and well mixed. From the observations, among the six mushroom samples, only two samples namely A. polytricha and L. rhinocerotis showed anticoagulant activities in the preliminary screening. Crude extracts of A. polytricha and L. rhinocerotis were tested for their In-vitro anti-platelet activity using fresh human blood. Platelet rich plasma 1.3 x 108 was obtained from the fresh human blood and the platelet aggregation activity was measured using spectrophotometer in percentage of transmittance values. Adenosine diphosphate was used to induce platelet aggregation in the study. Five concentrations (5 mg/mL, 10 mg/mL, 15 mg/mL, 20 mg/mL and 25 mg/mL) of crude mushroom extracts were tested. Anti-platelet activity was shown in L. rhinocerotis crude extract. The crude sample was then dialysed using dialysis tubing 12 kDa in distilled water overnight. The proteins were then precipitated out using acetone and the in-vitro anti-platelet activity test was performed again. The protein precipitated also showed anti-platelet aggregation activity in the study. Then, aqueous two phase system (ATPS) was done using 4 g of polyethylene glycol 50 % (PEG 8000) added with 2.9 g of phosphate 40 %. The anti-platelet aggregation activity was shown in the top phase of the aqueous two phase system (ATPS). The partially purified protein recovered in the top phase of the aqueous two phase system (ATPS) was then analysed using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Two bands of approximately 50 kDa and 55 kDa were observed in the gel. Non-denaturing PAGE (Native PAGE) was carried out and both of the bands were excised and tested. Anti-platelet aggregation activity was shown for both bands excised. As the crude extract and the partial purified crude enzyme of L. rhinocerotis possessed anti-platelet aggregation capacity, further studies on the enzyme/s involved and the mechanism are needed. The enzyme/s can be further purified and sequenced to identify the protein.